Encyclopedia of Analytical Chemistry 2019
DOI: 10.1002/9780470027318.a9258.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Methods forDNAAnalysis

Abstract: Applications of atomic force microscopy (AFM) to imaging of DNA with various structures, topologies, and complexes with proteins are reviewed. The emphasis is given to methods utilizing chemical functionalization of mica, enabling AFM visualization of different DNA structures. Special attention is given to the ability of AFM to image the dynamics of DNA at the nanoscale. The capabilities of time‐lapse AFM in aqueous solutions are illustrated by imaging of dynamic processes as transitions of local alternative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 154 publications
0
7
0
Order By: Relevance
“…1,2 Interaction between nucleosomes is a fundamental property that defines the assembly and function of chromatin. Studies over the past two decades have revealed highly dynamic features of nucleosomes that can explain regulatory processes at the chromatin level (e.g., see recent reviews [3][4][5] ). However, structural details and the mechanism underlying the assembly of nucleosomes in higher-order structures of chromatin and their dynamics remain unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Interaction between nucleosomes is a fundamental property that defines the assembly and function of chromatin. Studies over the past two decades have revealed highly dynamic features of nucleosomes that can explain regulatory processes at the chromatin level (e.g., see recent reviews [3][4][5] ). However, structural details and the mechanism underlying the assembly of nucleosomes in higher-order structures of chromatin and their dynamics remain unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…After measuring the thickness with the surface profilometer, the thermal evaporation tooling factor is adjusted to achieve optimum thickness. There are three operating modes for an AFM; contact mode, tapping mode, and non-contact modes [159]. In contact mode, there is physical contact between the probe and the sample surface.…”
Section: Surface Profilometermentioning
confidence: 99%
“…Despite contact mode offering high-speed scanning with high resolution, there is a higher chance of damaging the tip and the sample surface during scanning. Therefore, contact mode is usually used for flat and rigid surfaces [159]. In this thesis, surface roughness measurements are carried out in contact operating mode.…”
Section: (A) (B)mentioning
confidence: 99%
See 2 more Smart Citations